On the Origin of Pottery from Tel Miqne-Ekron - Gunneweg, Jan 1939-; Dôtān, Ṭrûdā 1922-2016; Perlman, Isadore 1915-1991; Gitin, Seymour (1986)
Provenience research on Mycenaean IIIC:1b and Philistine bichrome wares offers objective data regarding the origins of the Sea Peoples and their pattern of settlement in 12th-century B. C. Canaan. Forty-four ceramic specimens from the 1981 and 1982 excavations at Tel Miqne-Ekron were subjected to instrumental neutron activation analysis to learn where they were made. The main interest of this study was Mycenaean IIIC:1b wares found at Miqne. Iron Age I plain wares were analyzed because if they were made locally their composition could be a reference for other wares. It was deduced that all of the Mycenaean IIIC:1b pottery was made locally. Three of five pieces of Philistine ware from Miqne were locally made; the other two came from the Coastal Plain. Pottery of a "foreign" style, Mycenaean IIIC:1b, appearing at Miqne at the beginning of the Iron Age, was locally made. The classification of the pottery was accurate, for the wares are indistinguishable in appearance from the same kind found in their "homeland," showing that the potters in different places shared a common cultural affinity.